Establishing derived categorical responding in children with disabilities using the PEAK‐E curriculum. Issue 1 (20th October 2016) - Dixon, Mark R.; Belisle, Jordan; Stanley, Caleb R.; Speelman, Ryan C.; Rowsey, Kyle E.; Kime, Dena; Daar, Jacob H.
Abstract : The purpose of the study was to evaluate a procedure to generate derived categorical responding by three children with disabilities and to promote the emergence of untrained intraverbal categorical responses. In the study, three 4‐member equivalence classes including three stimuli (A, B, and C) and a category name (D) for each class were trained using a match‐to‐sample procedure. Test probes were conducted for categorical responding, including both a trained (D‐A) and two derived (D‐B, D‐C) relational responses, as well as the emergence of untrained intraverbal categorical responding (D‐A/B/C) throughout the study. Relational training was effective at promoting the emergence of categorical responding, and two of the three participants demonstrated the emergence of additional intraverbal responding without prior training. The results provide further evidence supporting the practical utility of stimulus equivalence as well as the PEAK‐E curriculum.